2014
DOI: 10.1007/s00592-014-0573-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of cytomegalovirus seropositivity and risk of mortality from diabetes

Abstract: Cytomegalovirus (CMV) infects 40 % of the world population and has been suggested to be associated with diabetes; however, no prospective study has ever examined diabetes mortality associated with the infection. A cohort of 14,404 non-diabetic adult participants aged 17-90 years from the Third National Health and Nutrition Examination Survey (1988-1994) was prospectively followed for mortality through 2006. CMV immunoglobulin G was measured by enzyme-linked immunosorbent assay and immunofluorescence assay. Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…It has been hypothesized that CMV also plays a role in the pathogenesis of neoplasms, such as colorectal cancer [Dimberg et al, ] and salivary gland mucoepidermoid carcinoma [Melnick et al, ]. In addition, the possible involvement of CMV in atherogenesis and the increased risk of diabetes mortality (HR 2.06, 95%CI, 1.05–4.06) described in patients with positive CMV serology is intriguing [Courivaud et al, ; Mendy et al, ]. In addition to the risk of developing a specific disease, in HIV‐positive subjects, CMV and EBV replication is positioned in a delicate balance with the host immune system and ART efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that CMV also plays a role in the pathogenesis of neoplasms, such as colorectal cancer [Dimberg et al, ] and salivary gland mucoepidermoid carcinoma [Melnick et al, ]. In addition, the possible involvement of CMV in atherogenesis and the increased risk of diabetes mortality (HR 2.06, 95%CI, 1.05–4.06) described in patients with positive CMV serology is intriguing [Courivaud et al, ; Mendy et al, ]. In addition to the risk of developing a specific disease, in HIV‐positive subjects, CMV and EBV replication is positioned in a delicate balance with the host immune system and ART efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Most reports of cytomegalovirus infection of the gastrointestinal tract are of immunosuppressed patients, such as those on immunosuppressive therapy or chemotherapy and those with malignant diseases, inflammatory bowel diseases, or human immunodeficiency virus infection (19,20). Furthermore, several authors have suggested that diabetes or glucose intolerance may cause cytomegalovirus infection (21)(22)(23). Our patient was neither immunodeficient nor on immunosuppressive therapy, but uncontrolled diabetes may have caused immune dysfunction, leading to cytomegalovirus enterocolitis.…”
Section: Discussionmentioning
confidence: 76%
“…In previous studies of CMV colitis in immunocompetent patients, the patient background (mean age, 61.1 years; DM, 13.6% [6/44] [9]; mean age, 65.6 years; DM, 33.3% [3/12] [10]; and mean age, 72.0 years; DM, 54.4% [6/11] [2]) suggested that elderly patients with DM are also at risk for CMV colitis. In addition, one prospective study reported that CMV infection doubled the risk of mortality from DM (HR, 2.06; 95%CI 1.05–4.06) [11]. Again, it has recently been reported that the in-hospital mortality and overall survival rates for CMV colitis patients without IBD are 29.5 and 60.7%, respectively, with all patients dying from their poor general condition, such as septic shock, instead of CMV colitis itself.…”
Section: Discussion/conclusionmentioning
confidence: 99%